Diabetic gymnastic effect to decrease blood glucose at PerwiraSari North Bekasi elderly - Meliyana, Ernauli (Jurnal Kesehatan AYURVEDA, 2014)
Background : Diabetes Mellitus is a desease caused by and poor life style and become causal of many  complication. Complication of Diabetes Mellitus can be prevented by controlling the blood sugar. Diabetic gymnastic is one way to decrease the blood sugar. On way to do was  doing the diabetes gymnastics which can decrease the blood sugar by increasing the glucose utilization by the active muscles so that decreasing glucose on blood.Research Objective: To knows an effect of the Diabetes gymnastics within decrease Blood sugar in old parents at Perwirasari RW 08 Bekasi Utara 2013.Method : Design of this research was using quasi-experimental with pretest-posttest with control group design as approach.Technique of sampling was total sampling with 20 respondent, and using paired t-test.Results : Result of this research wasp value ( 0,006 )<α  0,05. It means that Ho was rejected and H1 failed to reject.Conclusion: The analysis results shows that there is an effect of Diabetes gymnastics within decrease Blood sugar in oldparents at Perwirasari RW 08 Bekasi Utara 2013  Keyword                    :           Diabetes Gymnastic, Blood Sugar Level, DiabeticReferences                 :           (2008-2013)Number of Page        :           xv + 72